Discontinuation of angiotensin-converting enzyme inhibitors or beta-blockers and the impact on heart failure hospitalization rates. (1st December 2019) - Knafl, George J; Moser, Debra K; Wu, Jia-Rong; Riegel, Barbara
Abstract: Background: Adherence to evidence-based therapy is essential for optimal management of heart failure. Yet, medication adherence is poor in heart failure patients. The Ascertaining Barriers to Compliance Project decomposed the medication adherence process into initiation, implementation, and discontinuation stages, but electronic monitoring-based adherence analyses usually do not consider this process. Aims: The aim of this study was to describe individual-patient patterns of medication adherence from electronic monitoring data among adults with chronic heart failure, adherence types, and risk factors for increased all-cause hospitalization including measures of poor adherence such as discontinuation. Methods: Data from two prospective studies of adherence measured with electronic monitoring for heart failure patients were combined and restricted to monitoring of angiotensin-converting enzyme inhibitors and beta-blockers over an initial three-month period. Hospitalizations were recorded for this period as well as for a three-month follow-up period. Analyses were conducted using adaptive modeling methods to identify individual-patient adherence patterns, adherence types, and risk factors for an increased hospitalization rate. Results: Using electronic monitoring data for 254 heart failure patients, four adherence types were identified: highly consistent, consistent but variable, moderately consistent, and poorly consistent. Sixteen individually significant risk factors for increased hospitalization rates were identified and used to generate a multiple risk factors model. Medication discontinuation was the most important individual risk factor and most important in the multiple risk factors model. Conclusion: Discontinuation of angiotensin-converting enzyme inhibitors or beta-blockers increases hospitalization rates for heart failure patients. Interventions that effectively address this problem are urgently needed.